A Rare Case of Multiorgan Calciphylaxis in a Patient with Stage 5 Chronic Kidney Disease. (18th October 2018) - Ahmad, Abdulrahman; Albaghli, Ali; Michael, Adel; Refaat, Khaled; Omar, Mohammad; Ibrahim, Ahmad; Elmenshawy, Bahaa; Maher, Ashraf; Alramah, Rasha; Mikhail, Sami; Almahmid, Mustafa; Alenezi, Husain; et al.
Abstract : Calciphylaxis or calcific uremic arteriolopathy (CUA) is a potentially life-threatening vasculopathy involving the skin and subcutaneous tissues. It is usually associated with chronic kidney disease (CKD) and rarely with acute renal failure or predialysis patients. The clinical diagnosis of calcific uremic arteriolopathy relies on high index of suspicion. CUA is commonly associated with secondary hyperparathyroidism and high serum calcium and phosphate products. Moreover, using biopsy as a diagnostic tool is controversial, due to the high risk of poor wound healing and sepsis. Radiological studies usually reveal extensive calcification of branching vessels such as penile arteries, eventually leading to gangrene formation in extremities and penis. Histopathological analysis confirms the diagnosis of calcific uremic arteriolopathy and rules out the presence of malignancy. CUA is a systematic disease that involves multiple organs, and to the best of our knowledge this is the first reported case involving the penis, bladder, and eyes.